Learning to Learn Online - Page, Christina; Vincent, Adam (Open textbook library., 2018)
Learning to Learn Online helps you prepare for online learning success by introducing you to the online learning environment and your role as a learner within it. As you come to understand yourself as an self-directed learner, you will also be introduced to effective learning strategies: time management for online learners, information management, professional communication, and reading strategies. Welcome to your online learning journey!